Eight new species of the fern genus Polystichum (subg. Haplopolystichum; Dryopteridaceae) from limestone caves in Guizhou, China - Zhang, Li-Bing; Duan, Yi-Fan; Kropf, Matthias (Phytotaxa, 2019)
Eight new fern species of Polystichum subg. Haplopolystichum sect. Haplopolystichum (Dryopteridaceae) are described and illustrated from Guizhou Province, southwestern China. These eight species include P. anshunense, P. asperrimum, P. confusum, P. kropfii, P. libingii, P. macrodon, P. perditum, and P. yifanii. Each of these eight species was discovered from only 1–2 limestone caves showing extremely narrow distributions. Therefore, all are classified as Critically Endangered (CR) following IUCN Red List criteria.